2005
DOI: 10.1111/j.1365-2141.2005.05527.x
|View full text |Cite
|
Sign up to set email alerts
|

Red cell pyruvate kinase deficiency: molecular and clinical aspects

Abstract: SummaryRed cell pyruvate kinase (PK) deficiency is the most frequent enzyme abnormality of the glycolytic pathway causing hereditary non-spherocytic haemolytic anaemia. The degree of haemolysis varies widely, ranging from very mild or fully compensated forms, to life-threatening neonatal anaemia and jaundice necessitating exchange transfusions. Erythrocyte PK is synthesized under the control of the PK-LR gene located on chromosome 1. To date, more than 150 different mutations in the PK-LR gene have been associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
183
0
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(202 citation statements)
references
References 98 publications
8
183
0
11
Order By: Relevance
“…PK-deficient patients suffer from a variable degree of chronic hemolysis. Clinically, they manifest a highly variable phenotype, ranging from severe neonatal jaundice and anemia at birth, severe transfusiondependent chronic hemolysis, or moderate hemolysis with exacerbation during infection, to a fully compensated hemolysis without apparent anemia [Hirono et al, 2001;Zanella et al, 2005]. There is, however, no relationship between the residual enzymatic activity and the severity of hemolysis .…”
Section: Introductionmentioning
confidence: 99%
“…PK-deficient patients suffer from a variable degree of chronic hemolysis. Clinically, they manifest a highly variable phenotype, ranging from severe neonatal jaundice and anemia at birth, severe transfusiondependent chronic hemolysis, or moderate hemolysis with exacerbation during infection, to a fully compensated hemolysis without apparent anemia [Hirono et al, 2001;Zanella et al, 2005]. There is, however, no relationship between the residual enzymatic activity and the severity of hemolysis .…”
Section: Introductionmentioning
confidence: 99%
“…The degree of hemolysis can vary widely, from very mild and fully compensated forms to life-threatening anemia with transfusion dependency. 2 The treatment for PKD is mainly supportive, and consists of regular red blood cell transfusions, splenectomy and chelation therapy for iron overload. 3 Hematopoietic allogeneic stem cell transplantation (HSCT) has the potential to cure PKD.…”
mentioning
confidence: 99%
“…29 It is most likely that the incorporation of mutant R-PK subunits into the tetramer may interfere with the full restoration of PK activity in some erythroid cells. Since over 80% of reported R-PK mutations are missense mutations, 2,3 it seems that a gene-replacement strategy which inactivates the endogenous mutant R-PK gene might be required to achieve the complete cure of PK deficiency. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of the identified PK gene mutations are missense mutations, 2,3 and previous studies revealed that there were some kinetically aberrant enzymes, which showed normal intracellular stability in erythroid cells. These results suggest that R-PK subunits derived from the transgene might form heterotetramers with aberrant R-PK.…”
mentioning
confidence: 99%
See 1 more Smart Citation